Quality Analysis of JavaFX-Based Parking System Desktop Application Using ISO/IEC 25010 Model - Yunik Yuroidah; Lingga Wardana; Naufal Budiasan; Dhony Manggala Putra (Journal Innovation in Information and Computer Technology, 2026)
An organized and efficient parking system is essential for managing high-density parking areas. This study developed a JavaFX-based desktop parking system application with MongoDB database support, thermal printer and webcam integration. The application is designed to automatically record vehicle entry and exit transactions, print manual tickets, and display CCTV camera monitoring. Furthermore, the system also provides tariff management and transaction reporting features accessible through a dashboard. Software quality evaluation was conducted using the ISO/IEC 25010 model, with six main characteristics: Functionality, Reliability, Usability, Efficiency, Maintainability, and Portability. The results showed that the application met basic functional aspects, but still had weaknesses in performance efficiency and maintainability. Load testing using Apache JMeter indicated an exponential increase in response time under high load and an error rate of up to 8.82%. This study provides technical recommendations to improve system efficiency through indexing optimization, architectural refactoring to the MVC pattern, and integration of automated I/O devices such as parking barriers and ANPR.